2021
DOI: 10.1016/j.jadohealth.2020.09.007
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Support in Machismo and Acceptance of Violence Among Adolescents in Europe: Lights4Violence Baseline Results

Abstract: To analyze the potential association between social support, experiences of violence, and sociodemographic characteristics of adolescents and the likelihood of acceptance of violence and machismo in different European countries. Methods: Cross-sectional design. We recruited 1,555 participants ages 13e16 from secondary schools in Alicante (Spain), Rome (Italy), Iasi (Romania), Matosinhos (Portugal), Poznan (Poland), and Cardiff (UK). We used linear regression models to identify how social support from teachers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 35 publications
3
20
1
Order By: Relevance
“…The results of gender invariance in our study suggested that there were some differences between boys and girls in the CFA showing that boys reported more machismo and acceptance of violence than girls. Other studies that used the MVQ scale obtained the same results [22,27,42]. The differentiation in the socialization process between girls and boys may be an explanation of these results [43], where boys are educated to suppress emotions and display attitudes more related to violence.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The results of gender invariance in our study suggested that there were some differences between boys and girls in the CFA showing that boys reported more machismo and acceptance of violence than girls. Other studies that used the MVQ scale obtained the same results [22,27,42]. The differentiation in the socialization process between girls and boys may be an explanation of these results [43], where boys are educated to suppress emotions and display attitudes more related to violence.…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies supported a significant relationship between the macho attitudes of dating violence and the perpetration of TDV [25,26]. It was found that girls and boys who display macho attitudes are at increased risk of being a victim of dating violence [27]. Violence tolerance in a relationship has been identified as a risk factor for the increased frequency of abuse and perpetration of violence [28,29].…”
Section: Introductionmentioning
confidence: 93%
“…The results of this study also found that DV victimization among girls and boys was associated with higher levels of machismo. Machismo has been associated with an increase in the level of con icts in a relationship, making adolescents more vulnerable to becoming victims of violence and aggression and more emotionally dependent to the relationship [9]. The results of our study also showed that the likelihood of DV victimization in girls decreases with higher levels of violence acceptation.…”
Section: Discussionsupporting
confidence: 64%
“…There is also evidence that shows that there are social and economic factors associated with higher risk for DV, such as being of older age, lower socioeconomic conditions and belonging to a minority ethnic group [5,6]. An increased risk of DV victimization has been also reported by female and male adolescents who have been exposed to other forms of violence (childhood exposure or witnessing different forms of violence, bullying), poor quality friendships and family relationships and the presence of harmful attitudes such as sexism, machismo, or violence acceptability [7][8][9][10]. Conversely, a higher sense of attachment to school and teachers seems to be associated to a lower likelihood of both DV victimization and perpetration [11].…”
Section: Introductionmentioning
confidence: 99%
“…The family usually influences adolescent behavior and beliefs including levels of acceptance of violence in both boys and girls and, thereby determining to a greater or lesser extent the likelihood of their developing violent behavior. [43][44][45][46] Thus, parents who positively reinforce their children by giving them support and advice on how to handle the conflicts they must confront, promote alternatives to violence for solving their problems. 47,48 In an environment of positive family relations, determined by attachment, inductive, open, positive and empathic communication, the possibility of adolescents having aggressive conduct diminishes.…”
Section: Factors Involved In Violent Attitudesmentioning
confidence: 99%